Pengaruh Membaca Majalah Suara Muhammadiyah Dalam Rubrik Wawasan Keislaman Terhadap Pemahaman Keagamaan Masyarakat Di Kota Sorong - Rini, Rini; Masseni, Masseni (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
This study aims to determine the effect of reading Suara Muhammadiyah magazine in the rubric of Islamic insight on the religious understanding of the people in Sorong City. The research method used was quantitative with a sample of 30 people. Data were collected using a questionnaire with a Likert scale, and regression analysis was performed. The results showed a significant influence between reading on the religious understanding of the readers of Suara Muhammadiyah magazine in Sorong City. Therefore, Suara Muhammadiyah magazine needs to be used as an essential instrument in deepening the Islamic insight of the community.